The battle of learning modes: hybrid vs online learning in higher education - Ma'arif, Mahmuda; Santoso, Ridwan; Arif, Dikdik Baehaqi; Nuryana, Zalik (Journal of Education and Learning (EduLearn), 2025)
This study aims to compare the impact of hybrid learning and online learning on students' understanding of concepts at the college level. The type of research used in this study was a quasi-experimental control group design. This research data collection technique was obtained from 100 students who attended civic education lectures. The number of research samples was 100 students consisting of various study programs from the results of random sampling. Data was analyzed using independent sample t-test and paired sample t-test analysis techniques. The results indicate that hybrid learning is more effective in increasing students' understanding of material concepts. However, both types of learning have a significant impact on improving students' understanding of concepts. The findings of this research can be utilized to optimize Pancasila learning in higher education and provide comprehensive insights into the benefits of hybrid and online learning. The study concludes that hybrid learning, which combines face-to-face and online learning, is a highly effective form of learning in educational institutions. This is particularly relevant in the current global context, where educational institutions worldwide are grappling with the challenges posed by the COVID-19 pandemic.